Estandarización del proceso de Moldeo de fundición en la empresa FUNDI LASER- Ambato. - Taipe Tigse, Edwin Javier (2024)
Process standardization can produce better results by determining how, when, and what to do, so enhancing work techniques in each activity or subprocess. With the standardization of the foundry moulding process at FUNDI LASER, it is feasible to determine the timings for each action that the operator must complete. It also allows for the investigation of the factors involved in the process, such as material, machinery, methods, medium environment, and labour used, which will be analysed using Ishikawa's 5 M, among other continuous improvement tools for the topic's progress. Keywords: Standardization, Moulding process, Foundry, Parts